Heat pipe technology for electronic cooling and heat recovery systems / Ramadas Narayanan - Narayanan, Ramadas (2006)
Heat pipe is a two-phase heat transfer devices with extremely high effective thermal conductivity. They can be cylindrical or planar in structure. Heat pipes can be embedded in a metal cooling plate, which is attached to the heat source, and can also be assembled with fin stack for fluid heal transfer. Due to the high heat transport capacity, heat exchangers with heat pipes have become much smaller than traditional heat exchangers in handling high heat fluxes. With the working fluid in a heat pipe, heat can be absorbed on the evaporator region and transported to the condenser region where the vapor condenses releasing the heat to the cooling media. Heat pipe technology has found its increasing applications in Electronic Cooling and enhancing the thermal performance of Heat Recovery Systems in industrial sectors.